Kompensasi, Motivasi, dan Komitmen Kerja Terhadap Kinerja - Lenta Friska Purba; Dapot Ferdinan Alexius Butar Butar; Inri Septiana Romauli Simatupang; Samuel Benget Pratama Sihombing; Freddy Sikketang (Journal of Management and Bussines (JOMB), 2023)
This researcher aims to find out the impact of substandard wages, encouragement to work and commitment to the performance of PT. Mighty Steel. This research method is quantitative and quantitative descriptive. Multiple linear regression is a statistical analysis method used to determine the relationship involving one dependent variable with two or more independent variables. The results showed that the calculated F test value of 1.275 F was tabled at 1.66 and had a significance level of 0.000 <0.05 from the Y (bound) variable of Performance which could be explained through the X (free) variable compensation, motivation, and work commitment, and as many as 98 .9% is translated through different variables outside the variables applied in this Case Study. In conclusion, simultaneously that the variables of compensation (X1), motivation (X2), and work commitment (X3) have a significant good impact on work performance variables for PT. Sarana Baja Perkasa workers in Medan Raya Harbor 2 Kampung Salam Belawan. Keywords: Employee Performance, Work Commitment, Compensation, Motivation